Taking care : the story of nursing and its power to change our world - DiGregorio, Sarah (Harper, an imprint of HarperCollinsPublishers, 2023)
"Nurses have always been vital to human existence. A nurse was likely there when you were born and a nurse might well be there when you die. Familiar in hospitals and doctors' offices, these dedicated health professionals can also be found in schools, prisons, and people's homes; at summer camps; on cruise ships, and even at NASA. Yet despite being celebrated during the Covid-19 epidemic, nurses are often undermined and undervalued in ways that reflect misogyny and racism, and that extend to their working conditions--and affect the care available to everyone. But the potential power of nursing to create a healthier, more just world endures. The story of nursing is complicated. It is woven into war, plague, religion, the economy, and our individual lives in myriad ways. In Taking Care, journalist Sarah DiGregorio chronicles the lives of nurses past and tells the stories of those today--caregivers at the vital intersection of health care and community who are actively changing the world, often invisibly. An absorbing and empathetic work that combines storytelling with nuanced reporting, Taking Care examines how we have always tried to care for each other--the incredible ways we have succeeded and the ways in which we have failed. Fascinating, empowering and significant, it is a call for change and a love letter to the nurses of yesterday, today, and tomorrow."--